Investigation of hydrodynamic processes of the extinguishing device - Bogdevicius, Marijonas; Suslavicius, Vladimiras (Transport, 2005)
The main aim of the investigation is to develop an approach to investigate hydrodynamic processes in the extinguishing device. The mathematical model of the extinguishing device is presented where the flow of fluid and gas and the interaction of liquid with gas are taken into account. The flow of fluid in a hydraulic system is described by a system of equations of a hyperbolic type which is solved by a characteristics method. An instance of the mathematical simulation of the activity extinguishing device is shown. The dependence of recoil force is obtained.First Published Online: 27 Oct 2010